The New Precarization of Work: a Conceptual Map - Melges, Fabio; Gustavo Benini, Elcio; Cristina Costa Calarge, Tania; Pereira de Castro Pacheco, Adriano (Organizações & Sociedade, 2022)
The new precarization of work, flexible precarization, presents changes and significant new elements within the context of precarious work. As a historical manifestation, it has gradually been included within structural-economic and institutional-political reforms. This paper aims to propose a conceptual map of the new precarization of work. The conceptual map is a critical tool for developing a scientific investigation and links concepts, context, and theoretical influences to promote the advancement of research in the field of the object studied. Three dimensions embodied the proposed map: the context, synthesized in the rise of neoliberalism, in the hegemony of the financial sector, in productive restructuring, and in economic globalization; flexible practices, in the condition of manifestations and causalities of the social arrangements, exposed in terms of the naturalization of unemployment, economic fatalism, the emptying of the State, the sanctity of contracts, deregulation, work intensification, the capture of savoir faire, decentralization and deterritorialization of productive units, technocratic manipulations, the weakening of the unions, part-time or temporary work, outsourcing, and despecialization; and the categories, relational expressions identified as flexible capitalism, flexible business, flexibility (flexible regulation), social precarization, and the movement from formal to real subsumption. Providing a synthesized image that seeks to critically apprehend the concreteness of the real, the map can be used as a script for new research and to contribute to critiques in the field of organizational studies.